SOSIALISASI PENTINGNYA MEMBANGUN INTERAKSI SOSIALYANG POSITIF DI SEKOLAH DASAR KRISTEN IMMANUEL BATAM - Anastasya, Evangelyn; Purba, Gomgom; Butar-Butar, Putri Ayu Paulina; Zebua, Reni Wismawati (Unit Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This community service aims to explore the importance of building positive social interactions at SD Kristen Immanuel Batam. In the context of education, social interaction is considered as one of the key factors in students' cognitive and emotional development. Through a qualitative approach and case study, this study collected data from in-depth interviews, participant observation, and related document analysis. The results of the study indicate that constructive social interactions among students, teachers, and the community can improve academic achievement, strengthen self-confidence and empathy, and promote good moral values. Various strategies such as extracurricular activities, character education programs, and parental involvement in education have been implemented in schools to create an environment that supports positive social interactions. These findings indicate that collaboration between schools, parents, and the community is essential in building a culture of healthy interactions and supporting students' character development. Therefore, this community service not only provides insight into the importance of social interactions in schools but also presents recommendations for improving existing social programs, for a better future for future generations.